Method of obtaining lime-ammonia fertilizer - Alimov Umarbek Kadirberganovich; Hamdamova Zebuniso Shodmon's daughter; Hamdamov Doniyor Maxammdovich (Zien Journals, 2022)
The invention relates to the production of mineral fertilizers. Lime-ammonium fertilizer is obtained by mixing ammonium nitrate melt with crushed carbonate raw materials containing calcium carbonate or calcium and magnesium carbonate, granulating the mixture, drying and cooling the product, while before mixing with ammonium nitrate melt, crushed carbonate raw materials are treated with ammonium hydrosulfate with a concentration of 20 ÷ 45 wt.% in the ratio of mass parts 1:(0.01÷0.3). The crushed carbonate raw material has particle sizes from 0.8 mm to 1.5 mm, and granulation is carried out in a drum granulator at 80-90°C
Keywords: Lime-ammonia fertilizer; melt; mixture granulation; ammonium nitrate